2020
DOI: 10.1101/2020.02.28.20029272
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Closed environments facilitate secondary transmission of coronavirus disease 2019 (COVID-19)

Abstract: Objective: To identify common features of cases with novel coronavirus disease (COVID-19) so as to better understand what factors promote secondary transmission including superspreading events. Methods: A total of 110 cases were examined among eleven clusters and sporadic cases, and investigated who acquired infection from whom. The clusters included four in Tokyo and one each in Aichi, Fukuoka, Hokkaido, Ishikawa, Kanagawa and Wakayama prefectures. The number of secondary cases generated by each primary case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
287
0
11

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 320 publications
(311 citation statements)
references
References 2 publications
13
287
0
11
Order By: Relevance
“…It was considered that identifying clusters occurring in Japan with monitoring and isolating close contacts with the identified patients were prudent strategy and it would be able to comprehend the trend of COVID-19 infections in Japan. 4 However, since difference between those who were identified and those who actually had infections was so huge according to our findings, Japan might not have comprehended the epidemic dynamics occurring in the nation.…”
Section: Discussionmentioning
confidence: 63%
“…It was considered that identifying clusters occurring in Japan with monitoring and isolating close contacts with the identified patients were prudent strategy and it would be able to comprehend the trend of COVID-19 infections in Japan. 4 However, since difference between those who were identified and those who actually had infections was so huge according to our findings, Japan might not have comprehended the epidemic dynamics occurring in the nation.…”
Section: Discussionmentioning
confidence: 63%
“…Assuming our estimates are correct, a substantial proportion of these infected persons likely had only a mild or asymptomatic course of disease [9,17] and therefore did not seek medical care and were not detected by the surveillance system. Preliminary analysis of the offspring distribution among infected individuals in the detected clusters around Japan has shown that approximately 80% of cases do not produce secondary infections (i.e., their reproduction number is equal to zero) [50]. Because most of the clusters have been linked to the known cases and could be traced back in time, we argue that there is still a window of opportunity for containment of the disease and only some small fraction of the infections may drive the epidemic [14].…”
Section: Discussionmentioning
confidence: 99%
“…Our R 0 obtained before VECSC was smaller than the previous studies , however, reproduction numbers in VECSC period and after VECSC were almost comparable. However, an earlier study [11] estimated R 0 in Japan All rights reserved. No reuse allowed without permission.…”
Section: Discussionmentioning
confidence: 96%